The Activity Test of Soursop Fruit Juice (Annona muricata L) on Decreasing Cholesterol Levels in Male Mice (Mus musculus) - Edy Sapada; Wita Asmalinda; Fatimah Eka Mariana (Universitas Aisyah Pringsewu, 2022)
The increased cases of hypercholesterolemia in Indonesia encourage the public to make prevention and treatment efforts. Soursop fruit is an option because it has properties to lower blood cholesterol levels be a potential source of antioxidants, which can inhibit oxidation reactions by binding to free radicals and highly reactive molecules. The aim of this study was to determine the effect of soursop fruit juice (Annona muricata L) on the total blood cholesterol levels of male mice (Mus musculus). This type of research is an experimental study of benefit testing, with a comparison group (pre-test and post-test with control group design). This research was conducted at the Pharmacology and Natural Materials Laboratory of STIK Siti Khadijah Palembang for 21 days. The sample in this study was male mice aged 6-8 weeks with an average body weight of 20-30 grams of normal mice, which met the inclusion and exclusion criteria. The number of samples is 25 male mice. There was a significant relationship between the cholesterol levels of mice before and after being given soursop fruit juice. It was concluded that the administration of soursop fruit juice effected reducing blood cholesterol levels. It is recommended that further research be conducted on human samples. Abstrak: Meningkatnya kasus hiperkolesterolemia di Indonesia mendorong masyarakat untuk melakukan usaha pencegahan dan pengobatan. Buah sirsak menjadi pilihan karena memiliki khasiat untuk menurunkan kadar kolesterol darah, menjadi sumber antioksidan yang potensial. yang mampu menghambat reaksi oksidasi dengan mengikat radikal bebas dan molekul yang sangat reaktif. Tujuan penelitian ini adalah untuk mengetahui pengaruh jus buah sirsak (AnnonamuricataL) terhadap kadar kolesterol total darah mencit jantan (Mus musculus). Jenis penelitian ini adalah penelitian eksperimental uji manfaat, dengan kelompok pembanding (pre-test and pos-test with control group design). Penelitian ini dilakukan di laboratorium Farmakologi dan Bahan Alam STIK Siti Khadijah Palembang selama 21 hari. Sampel dalam penelitian ini adalah mencit jantan berusia 6–8 minggu dengan rerata berat badan mencit normal adalah 20-30 gram, yang memenuhi kriteria inklusi dan eksklusi. Jumlah sampel adalah 25 mencit jantan. Ada hubungan yang bermakna kadar kolesterol mencit sebelum dan setelah diberikan jus buah sirsak. Disimpulkan bahwa pemberian jus buah sirsak berpengaruh terhadap penurunan kadar kolesterol darah. Disaran untuk dilakukan penelitian lebih lanjut pada sampel manusia.